The image of Ukraine in South Korean media: July 2017 - June 2018 - Andrii Ryzhkov; Nayelli Lopez Rocha (Cхід)
The article offers an empirical analysis of the ways in which South Korean press portrays Ukraine. To do this, this paper focuses on three major daily newspapers of the Republicof Korea, Chosun Ilbo, JoongAng Ilbo and DongA Ilbo. The article offers a 12-month long diagnosis of the news (July 1, 2017 - June 30, 2018), which discloses the agenda of objects and attributes regardingUkraine. Therefore this study helps to explore the processes and factors that generate media image and communicate it to South Korean society. As far as methodology is concerned, a combination of two aspects was employed in this study. The first was a quantitative analysis of news reports. The second was a qualitative interpretation applied to find out the evaluative undertones of the stories based on content analysis. To this end, all the 309 news reports analyzed in this paper are classified as positive, negative and neutral and grouped - according to their topic - into 8 major categories: Economy, Politics, International Relations, Society, Culture, Public Security, Sports and Miscellanea. This study focuses on all the news reports onUkraine, including those, which briefly mention the country, its territories or people.